Phosphorylation of the DNA-binding domain of nonhistone high-mobility group I protein by cdc2 kinase: reduction of binding affinity. - Reeves, R (1991)
Mammalian high-mobility group I nonhistone protein (HMG-I) is a DNA-binding chromatin protein that has been demonstrated both in vitro and in vivo to be localized to the A + T-rich sequences of DNA. Recently an unusual binding domain peptide, "the A.T-hook" motif, that mediates specific interaction of HMG-I with the minor groove of DNA in vitro has been described. Inspection of the A.T-hook region of the binding domain showed that it matches the consensus sequence for phosphorylation by cdc2 kinase. Here we demonstrate that HMG-I is a substrate for phosphorylation by purified mammalian cdc2 kinase in vitro. The site of phosphorylation by this enzyme is a threonine residue at the amino-terminal end of the principal binding-domain region of the protein. Labeling of mitotically blocked mouse cells with [32P]phosphate demonstrates that this same threonine residue in HMG-I is also preferentially phosphorylated in vivo. Competition binding studies show that cdc2 phosphorylation of a synthetic binding-domain peptide significantly weakens its interaction with A + T-rich DNA in vitro, and a similar weakening of DNA binding has been observed for intact murine HMG-I protein phosphorylated by the kinase in vitro. These findings indicate that cdc2 phosphorylation may significantly alter the DNA-binding properties of the HMG-I proteins. Because many cdc2 substrates are DNA-binding proteins, these results further suggest that alteration of the DNA-binding affinity of a variety of proteins is an important general component of the mechanism by which cdc2 kinase regulates cell cycle progression.